Please give me the best way for solving the problem of class 9^{th} ncert math of Polynomials chapter of math of class 9^{th} of exercise 2.5 of question no 9(2) what is the tricky way for solving this question Verify:(ii) x3–y3 = (x–y)(x2+xy+y2)

AnilSinghBoraGuru

# Verify:(ii) x3–y3 = (x–y)(x2+xy+y2) Q.9(2)

Share

We know that,(x–y)

^{3}= x^{3}–y^{3}–3xy(x–y)⇒ x

^{3}−y^{3 }= (x–y)^{3}+3xy(x–y)⇒ x

^{3}−y^{3 }= (x–y)[(x–y)^{2}+3xy]Taking (x+y) common ⇒ x

^{3}−y^{3 }= (x–y)[(x^{2}+y^{2}–2xy)+3xy]⇒ x

^{3}+y^{3 }= (x–y)(x^{2}+y^{2}+xy)